A technical performance analysis of soccer games - Espinosa-Sanchez, M. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Biomechanical aspects in the technical performance of soccer players defined the characteristics of their skills (Luhtanen, 2004). These allow the identification of determinants of successful technical performance during the game. For this study, the set of technical elements are actions with and without the ball and those of the goalkeeper (Bruggermann, 1996; Cantarero, 1995; Vidinic, 1988), which are hierarchically organized to facilitate the analysis (Brown, 1992; Espinosa, 2002; Koch, 1998; Vidinic, 1988). The semifinal ( MEX vs JAP ) and final (MEX vs BRA) of London 2012 were analyzed. Methods: A careful observation was made, using the program Utilius Fairplay 5 © of the official video broadcast in TV. The following apparent aspects had been considered: a rating of three height ranges in the displacement of the ball, three force ranges of the player, two ranges of the distance of the ball, and the player`s displacement with or without the ball taking into account the permitted and probable body parts. It is almost impossible to identify which zone of the ball is struck, and some times either which is the part of the foot that makes contact. Results: The technical elements were summed for every 15 minutes of the game, and in each soccer field side. Examples of actions (semifinal/final) are: Hitting the ball (487/311) with the inside of the foot (267/146) of these 17 were carried out during the first 15 minutes at the final game, 11 moved the ball with the floor, 2 with poor force, 4 for a short and 6 large distances; with the outside of the foot (34/47) and with the head (30/52) of these 29 jumping during the fourth 15 minutes at the semifinal game. Receptions (468/282) with the inside of the foot (187/132), hitting at reception (88/66). Change of direction (69/75); feint with body rotation (89/58); sprint run (34/72); defensive blocking (285/386), of these from front (128/110). Goalkeeper action`s (74/130), trapping the ball with both hands (1/8). Discussion: This study would be an assessment to the technical movements. The results could be an indication of the technical preparation of the team`s players, the intensity of the game, but probably also the coach strategy proposed to address the opposing team.